Local Library Authorities in South Indian Public Libraries Acts: A Case Study - Barman Mitali; Lahkar Narendra (Libri)
Legislation pertaining to public libraries is a helpful instrument for attaining state-mandated library services, financial support, resource and network sharing among libraries, and administrative effectiveness. In order to better understand the history of Public Libraries Acts in the Southern Indian states, this paper looks at a number of public library development aspects. Another focal point of the study is a comparative analysis of the provision of involvement of Local Library Authorities as well as their role and governance model in the Southern Indian states of India. The current work is based on data gathered from primary and secondary sources. To study the Public Libraries Acts of the southern states of India, the respective state government’s gazetteer notification and website of RRRLF were used as sources for data collection. The study has extensively analyzed the Local Library Authorities of Public Libraries Acts of South Indian States and made a comparative study among the different elements of the Local Library Authorities of the Public Libraries Acts. The study finds out that Kerala state has taken several distinctive steps in the development of its Local Library Authorities, including the establishment of block-level libraries. The study reveals that the local community and the Local Library Authorities have a tight relationship and are mutually fulfilling their objectives. Despite having sufficient provision for engagement of Local Library Authorities in the Public Libraries Act of the southern states, there is still debate about the proper implementation of the Acts.